Mall Models: How Abercrombie & Fitch Sexualizes its Retail Workers. (26th April 2016) - Walters, Kyla
Corporate branding strategies entail showcasing a store's "look" using retail workers' bodies. In this research note, I describe how clothing chain Abercrombie & Fitch embeds its brand of sexuality onto visible retail workers—employees the company long referred to as "models." Drawing on interview and observational research, I examine their labor practices of cultivating workers' appearances by imposing their employee "look policy, " recruiting workers for "the look, " stratifying employees based on appearance, employing shirtless greeters, and creating a shopping environment that encourages customers to sexually harass workers. The discussion highlights the discriminatory nature of these labor practices and resulting negative experiences for workers.